Learning to Write Prescriptions for Soft Drug Forms - Jalilova D.M.; Lapasova M.SH; Burkhanova D.S. (Genius Journals, 2022)
In daily practice, patients are recommended to use ointments, liniments, creams, gels, pastes, suppositories prepared from many medicinal plants, animal products and chemical compounds for the treatment of various diseases. Ointments, liniments, creams for students studying medicine. In order to study gels, pastes, suppositories, taking into account the importance of the composition of the preparation of solid forms of medicine and the rules of writing a prescription for them, a summary of general understanding was created for the students of the medical school.
Keywords: Soft drug forms; ointment; gel; suppositories